EKRANISASI NOVEL AIR MATA TUHAN KARYA AGUK IRAWAN MN KE DALAM FILM AIR MATA SURGA KARYA HESTU SAPUTRA - Findiar Mina Rosie; Engkin Suwandana; Wawan Hermawan (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This study aims to describe and explain the process of granularity, character, differences, and the value of character education that is in the novel Air Mata Tuhan by Aguk Irawan MN into the movie Air Mata Surga directed by Hestu Saputra using the theory of ecranization because ecranization is the only key to dissect the problem on the filmed novel. The type of research used in this research is descriptive research type, with qualitative approach. The subject or source of data used in this study is a novel document titled Tears of God by Aguk Irawan and a film titled Air Mata Surga directed by Hestu Saputra along with the transcript of the film. The instrument or research tool is the researcher himself. Data analysis technique using the theory of ekranisasi through comparison between the novel Air Mata Tuhan by Aguk Irawan with the film Air Mata Surga directed by Hestu Saputra. The validity of this research data is done with in-depth description and triangulation. The results of the research resulted in the process of ecranization that occurs on the elements of plot and character that is there is shrinkage, addition, and change varies. Differences in novels and movies are caused by the appearance of a story whose purpose is for the story to flourish and to vary. And lastly there are 4 grades of character education contained in novels and movies. The appearance of the value of character education because of the conflict that occurs is a story that has relevance to life in society in general. Keywords: Ekranisasi, Novel, Film.